Evaluasi Program Jaminan Persalinan (Jampersal) di Puskesmas Mayang Kecamatan Mayang Kabupaten Jember Tahun 2012 (The Evaluation Jampersal program at Public Health Centre Mayang Subdistrict Mayang Regency Jember at 2012 years) - Rifka Dwita Fitri; Abu Khoiri; Dyah Kusworini (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
According to data from the District Health Office of Jember in 2012, the highest infant mortality rate is in Mayang Public Health Centre. Jampersal can encourage acceleration achievement of MDGs 4 and 5 is to reduce child mortality, and improve maternal health. The purpose of the research to know the cause of the high infant mortality rate at Mayang Public Health Centre and low coverage compared to the target. Method of the research use descriptive. The subjects in this research are a doctor, midwife, jampersal target, and public figures .An informer in this research totaled 34 informer.Tekhnik data analysis using triangulation. Based on research, input is appropriate infrastructure of.The input that is not appropriate human resources type of service and financing.The process is no corresponding to technical instruction jampersal. Output is scope child and maternal health and the infant mortality rate in 2013. Child and maternal health coverage 2013 less than a targets but better than in 2012.Infant mortality in puskesmas mayang 2013 also decrease compared to the year 2012. Based on the evaluation can be concluded that program jampersal average there is a discrepancies in every element in the system with technical guide Jampersal program. Keyword: Jampersal, target, scope